Clinical Safety and Efficacy of Wenxin Keli-Amiodarone Combination on Heart Failure Complicated by Ventricular Arrhythmia: A Systematic Review and Meta-analysis - Zheng, Rui; Tian, Guihua; Zhang, Qin; Wu, Lin; Xing, Yanwei; Shang, Hongcai (Frontiers in Physiology, 2018)
Objectives: To evaluate possible adverse effects and efficacy of Wenxin keli (WXKL)-amiodarone combination on heart failure complicated by ventricular arrhythmia. Methods: Nine electronic literature databases (the Cochrane Library, PubMed, EMBASE, IPA, AMED, CBM, CNKI, VIP and WanFang) were searched up to February 2018. Two authors extracted data and assessed risk of bias of the included studies independently. Randomized controlled trials (RCTs) and quasi-RCTs about WXKL-amiodarone combination and amiodarone alone were eligible for comparison. Results: Thirteen trials involving 1126 patients were included. Risk of bias was assessed as high in three studies and unclear in the remaining ten studies. Six trials reported adverse events (AE). There was no obvious difference between WXKL-amiodarone combination group and amiodarone group in reported AEs (OR 0.64; 95%CI 0.39 to 1.07). The total effective rate of WXKL-amiodarone combination group was higher than that of amiodarone group (RR 1.22; 95%CI 1.16 to 1.29). The pooled results showed that the combination group was more effective in reducing heart rate (MD -2.25; 95%CI -2.61 to -1.88, P=0.46, I2=0%), the frequency of ventricular premature complexes (MD -2.03; 95%CI -2.41 to -1.65) and QT dispersion (MD 5.59; 95%CI 3.60 to 7.58). Conclusion: The WXKL-amiodarone combination may be safe and shows more protective effects on heart failure combined with ventricular arrhythmia compared with amiodarone alone. Further research is warranted, ideally involving large, prospective, rigorous trials, in order to confirm these findings.